DEVELOPING ESP LISTENING COMPREHENSION IN THE CONTEXT OF RADIO AND TV NEWS – THE USE OF STRATEGIES (Živi jezici: Journal for Foreign Languages and Literatures, 2017)
The pedagogical value of of an authentic input (radio and TV news) for developing listening comprehension was examined on 83 students of economics studying ESP at B1-B2 level. The aim of the research was to determine whether the exposure to radio and TV news results in the improvement in listening comprehension after two semesters of instruction, and in what format the potential improvement is more pronounced: audio or video. Based on the pre-test post-test design, it was found that the experimental group respondents, who had been exposed to the systematic listening comprehension strategies instruction, outperformed control group, as well as achieved higher scores in TV news than radio news listening tasks. The results in favor of video format and the use of listening comprehension strategies confirm the importance of their implementation in the classroom.
Keywords: radio and TV news, listening and comprehension skills, speech comprehension strategies, nonverbal communication